Altered sphingolipid function in Alzheimer's disease; a gene regulatory network approach - Giovagnoni, Caterina; Ali, Muhammad; Eijssen, Lars M.T.; Maes, Richard; Choe, Kyonghwan; Mulder, Monique; Kleinjans, Jos; del Sol, Antonio; Glaab, Enrico; Mastroeni, Diego; Delvaux, Elaine; Coleman, Paul; et al. (Neurobiology of aging, 2021)
•This study addressed the role of sphingolipid (SL)-related genes in Alzheimer's disease (AD).•PTGIS, GBA, ITGB2 presented both DNA hydroxymethylation and expression changes in AD.•A gene regulatory network analysis was used to reconstruct phenotype-specific networks.•Perturbation of CAV1 normalized the gene expression state of 16 genes in the AD network.•Our results provide further evidence on the involvement of SL-related changes in AD. Sphingolipids (SLs) are bioactive lipids involved in various important physiological functions. The SL pathway has been shown to be affected in several brain-related disorders, including Alzheimer's disease (AD). Recent evidence suggests that epigenetic dysregulation plays an important role in the pathogenesis of AD as well. Here, we use an integrative approach to better understand the relationship between epigenetic and transcriptomic processes in regulating SL function in the middle temporal gyrus of AD patients. Transcriptomic analysis of 252 SL-related genes, selected based on GO term annotations, from 46 AD patients and 32 healthy age-matched controls, revealed 103 differentially expressed SL-related genes in AD patients. Additionally, methylomic analysis of the same subjects revealed parallel hydroxymethylation changes in PTGIS, GBA, and ITGB2 in AD. Subsequent gene regulatory network-based analysis identified 3 candidate genes, that is, SELPLG, SPHK1 and CAV1 whose alteration holds the potential to revert the gene expression program from a diseased towards a healthy state. Together, this epigenomic and transcriptomic approach highlights the importance of SL-related genes in AD, and may provide novel biomarkers and therapeutic alternatives to traditionally investigated biological pathways in AD.